2007
DOI: 10.1080/13691050701208474
|View full text |Cite
|
Sign up to set email alerts
|

Wasting semen: Context and condom use among the Maasai

Abstract: negative impact on quality of sex; the wasting of sperm; and the 'otherness' of condoms. The implications of these findings for condom provision and uptake are considered in the discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Research from Tanzania, 79 Nigeria, 85,91,92 South Africa, 89,93,94 Kenya, 73,95 and Zambia 96 supports the observation that these beliefs about masculinity and femininity overlap with the belief that the core purpose of sexual interaction is a demonstration of virility and fertility. Sexual activity that does not involve the deposit of semen in the vagina has been described as 'wasting semen' and inhibiting the pleasure of both partners in Tanzania, 79 Kenya, 73,95 Nigeria 92 and Zambia.…”
Section: Inside Cognitions: Beliefs About Masculinity Femininity Andmentioning
confidence: 80%
See 2 more Smart Citations
“…Research from Tanzania, 79 Nigeria, 85,91,92 South Africa, 89,93,94 Kenya, 73,95 and Zambia 96 supports the observation that these beliefs about masculinity and femininity overlap with the belief that the core purpose of sexual interaction is a demonstration of virility and fertility. Sexual activity that does not involve the deposit of semen in the vagina has been described as 'wasting semen' and inhibiting the pleasure of both partners in Tanzania, 79 Kenya, 73,95 Nigeria 92 and Zambia.…”
Section: Inside Cognitions: Beliefs About Masculinity Femininity Andmentioning
confidence: 80%
“…Sexual activity that does not involve the deposit of semen in the vagina has been described as 'wasting semen' and inhibiting the pleasure of both partners in Tanzania, 79 Kenya, 73,95 Nigeria 92 and Zambia. 96 In several of these studies, men report and are reported to make holes in condoms to ensure their sperm or semen can escape into the vagina, and both men and women speak of 'tricking' their partner into condomless sex.…”
Section: Inside Cognitions: Beliefs About Masculinity Femininity Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Some campaigners have further claimed that condoms are deliberately impregnated or laced with HIV to 'wipe them out' 15 . In some African cultures, sperm are taken to be of key importance in 'nourishing' the women and in child development during pregnancy, when repeated sex is undertaken 16 . The Masai in East Africa reject condom use as a 'waste' of sperm and this belief strongly influences their sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although actual HIV rates are difficult to obtain due to governmental restrictions on census and data collection differentiation by tribal identification, sexual traditions and social norms place the Maasai people of Tanzania at high risk for sexually transmitted diseases. Maasai norms and traditions include esoto (coerced sexual initiation of pre-pubes-June 2014.…”
Section: Background and Contextmentioning
confidence: 99%